Fahr’s Syndrome in a Patient with Chronic Hypocalcemia and Basal Ganglia Calcification: A Case Report - Atefeh Yousefi; Narges Mirzaeiilali (Journal of Mazandaran University of Medical Sciences)
Hypoparathyroidism is an endocrine disorder characterized by hypocalcemia, hyperphosphatemia, and inappropriately low levels of parathyroid hormone. In this report, we present the case of a 19-year-old male patient with hypoparathyroidism, basal ganglia calcification, and a subsequent diagnosis of Fahr's syndrome. The patient presented with a decreased level of consciousness, metabolic acidosis, hypocalcemia, and elevated urea and creatinine levels. Despite impaired renal function and the expected elevation of parathyroid hormone (PTH), laboratory tests revealed a decreased PTH level, leading to a diagnosis of hypoparathyroidism. The patient had a history of seizures at the age of two, which he attributed to hypocalcemia. Since then, he had not undergone any regular follow-up. The patient required hemodialysis due to advanced renal failure. Owing to refractory hypocalcemia, he was prescribed high-dose intravenous and oral calcium, along with oral calcitriol. After a prolonged course of treatment, serum calcium levels eventually normalized. The patient also reported occasional muscle cramps, skin discoloration, brittle nails, neurological and psychiatric symptoms, as well as cataracts in recent years. Due to the reduced level of consciousness, a brain computed tomography (CT) scan was performed, which revealed basal ganglia calcification. In light of the hypoparathyroidism diagnosis and the CT findings, the patient was diagnosed with Fahr's syndrome. In patients presenting with hypocalcemia and evidence of basal ganglia calcification, parathyroid hormone levels should be assessed to evaluate for hypoparathyroidism and to rule out Fahr’s syndrome